Evaluation of the efficacy of acetone-dried common carp pituitary during induced breeding of African catfish (Clarias gariepinus) after an extremely long-term storage - Tamás Szabó; Ferenc Radics; Ádám Borsos; Barnabás Fodor; Tamás Müller; Béla Urbányi; László Horváth (Aquaculture Reports, 2023)
Hypophysation is the oldest and most widely used method of induced fish breeding. In practice, common carp (Cyprinus carpio) pituitary is one of the most commonly used agents to induce ovulation. The active ingredients of pituitary (glycoprotein) are very susceptible to fast degradation, therefore the glands must be preserved immediately after collection. Preservation is usually carried out in acetone which dehydrates and defattens the glands.The aim of our experiments was to investigate the efficacy of an extremely long-stored batch of pituitary gland collected in 1967. The biological potential of the glands was assessed through reproductive indices recorded during induced breeding of African catfish (Clarias gariepinus). The experiments were performed in October 2020. One group of females was treated with acetone-dried carp pituitary collected in 1967 and the other group was injected with pituitary collected in the year prior to the experiments. To assess the effectiveness of the pituitary treatment the following reproductive traits were determined: ratio of ovulated females, relative weight of the stripped eggs and the residual ovary, fertilization and hatching rates. The statistical methods used did not indicate a significant difference between the two groups for any of the reproductive indices, which means that the pituitary gland collected in 1967 remained effective after 53 years.